Reduction in oxidative stress levels in the colonic mucosa without fecal stream after the application of enemas containing aqueous Ilex paraguariensis extract - Cunha,Fernando Lorenzetti da (2011)
PURPOSE: To evaluate the antioxidant effects of enemas containing aqueous extract of Ilex paraguariensis, comparing segments with and without fecal stream and correlating the segments with the duration of intervention. METHODS: Twenty-six Wistar rats were subjected to a diversion of the fecal stream in the left colon by a proximal colostomy and distal mucosal fistula. The rats were distributed randomly into two experimental groups of 13 animals each based on the time of sacrifice after surgical procedure (two or four weeks). Each group was then divided into two experimental subgroups that received either second daily enemas containing 0.9% saline solution or aqueous extract of Ilex paraguariensis at 0.2g/100g. Colitis was diagnosed by histopathological analysis and the detection of oxidative tissue damage by measuring the levels of malondialdehyde. The Mann-Whitney test was used to compare the tissue levels of malondialdehyde between colon segments with and without fecal stream in each experimental group, and the Kruskal-Wallis test was used to verify the variance between the levels of oxidative stress according the duration of the irrigation; both tests determined significance at 5% (p<0.05). RESULTS: The levels of malondialdehyde in the animals subjected to intervention in the colon with saline with and without fecal stream after two and four weeks of irrigation were 0.05±0.006 and 0.06±0.006, and 0.05± 0.03 and 0.08 ±0.02, respectively. The malondialdehyde levels in the animals irrigated with Ilex paraguariensis with and without fecal stream after two and four weeks of irrigation were 0.010±0.002 and 0.02±0.004, and 0.03±0.007 and 0.04±0.01, respectively. After two and four weeks of intervention, the levels of malondialdehyde were lower in the animals irrigated with Ilex paraguariensis regardless of the time of irrigation (p=0.0001 and p=0.002, respectively). CONCLUSION: The daily rectal application of enemas containing aqueous extract of Ilex paraguariensis decreases oxidative tissue damage in the colon without fecal stream regardless of the time of irrigation.